THE TYPOLOGY OF NEO ROMANTIC IDEOLOGIC-AESTHETIC CONSCIOUSNESS IN LITERARY AND CRITICAL WRITINGS OF W. B. YEATS AND LESYA UKRAINKA - Hedzyk, O. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In this article it is realized an attempt of comparative analysis of literary-critical works of W.B.Yets and Lesia Uktainka on the issue of early modernism. It is assured the antimimetic character if its conceptions of symbolism and neo romanticism accordingly. It is analysed the attitude of both artists to the theory of "pure art." It is outlined the value of their dramatic activities for the development of modern (poetic) drama.